Mechanistic concepts involved in biofilm associated processes of Campylobacter jejuni: persistence and inhibition in poultry environments - Iulia A. Bundurus; Igori Balta; Ioan Pet; Lavinia Stef; Cosmin Alin Popescu; David McCleery; Joanne Lemon; Todd Callaway; Alastair Douglas; Nicolae Corcionivoschi (Poultry Science)
ABSTRACT: Campylobacter species, predominantly Campylobacter jejuni, remains a significant zoonotic pathogen worldwide, with the poultry sector being the primary vector for human transmission. In recent years. there has been a notable rise in the incidence of human campylobacteriosis, necessitating a deeper understanding of the pathogen’s survival mechanisms and transmission dynamics. Biofilm presence significantly contributes to C. jejuni persistence in poultry and subsequent food product contamination, and this review describes the intricate processes involved in biofilm formation. The ability of Campylobacter to form biofilms on various surfaces, including stainless steel, plastic, and glass, is a critical survival strategy. Campylobacter biofilms, with their remarkable resilience, protect the pathogen from environmental stresses such as desiccation, pH extremes, biocides and sanitizing agents. This review explores the molecular and genetic mechanisms of C. jejuni biofilm formation, highlighting regulatory genes involved in motility, chemotaxis, and stress responses. Flagellar proteins, particularly flaA, flaB, flaG, and adhesins like cadF and flpA, are identified as the main molecular components in biofilm development. The role of mixed-species biofilms, where C. jejuni integrates into existing biofilms of other bacteria to enhance pathogen resilience, is also discussed. This review also considers alternative interventions to control C. jejuni in poultry production, in the context of increasing antibiotic resistance. It explores the effectiveness of prebiotics, probiotics, synbiotics, bacteriocins, bacteriophages, vaccines, and organic acids, with a focus on their mechanisms of action in reducing bacterial colonization and biofilm formation. Studies show that mixtures of organic acids and compounds like Carvacrol and Eugenol significantly downregulate genes linked with motility and adhesion, thereby disrupting biofilm integrity. It discusses the impact of environmental factors, such as temperature and oxygen levels on biofilm formation, providing insights into how industrial conditions can be manipulated to reduce contamination. This paper stresses the need for a multifaceted approach to control Campylobacter in poultry, integrating molecular and genetic insights with practical interventions. By advancing our understanding of biofilm dynamics and gene regulation, we aim to inform the development of more effective strategies to enhance food safety and protect public health.